The Influence of Knowledge about Filing and Paying Local Taxes and Service Quality on Satisfaction in Filing and Paying Local Taxes of People in San Klang Subdistrict Administrative Organization, San Pa Tong District, Chiang Mai Province. - คุณชมภู ทิวารักษ์; คำขันแก้ว พงศ์ศิริ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aimed to investigate the influence of knowledge about local tax filing and payment, as well as service quality, on the satisfaction of residents with the process of local tax filing and payment in San Klang Subdistrict Administrative Organization, San Pa Tong District, Chiang Mai Province. A quantitative research methodology was employed, with a sample of 262 residents who had paid local taxes. The participants were selected using accidental sampling. The research instrument was a questionnaire that had been validated for content accuracy and reliability, with a Cronbach’s Alpha coefficient of 0.943. Data were analyzed using multiple regression analysis. The findings revealed that both knowledge of local tax filing and payment and service quality had a statistically significant positive influence on satisfaction with local tax filing and payment. Notably, service quality had a greater impact than tax-related knowledge. The coefficient of determination (R²) was 0.811, indicating that the two variables could explain 81.1% of the variance in satisfaction levels. These findings can be applied to improve the efficiency of local tax collection systems and enhance the quality of services provided by public sector organizations, thereby fostering sustainable revenue generation and greater public cooperation.